Neuroprotective effect of minocycline against acute brain injury in clinical practice: A systematic review. (April 2021) - Strickland, Ben A.; Bakhsheshian, Joshua; Emmanuel, Ben; Amar, Arun; Giannotta, Steven L.; Russin, Jonathan J.; Mack, William
Highlights: Minocycline is highly lipophilic with high penetrance across the blood brain barrier. Few investigations into minocycline as a neuroprotectant in humans exist. Minocycline has been mostly investigated in the ischemic stroke population with varying results. Abstract: Acute brain injury is a leading cause of morbidity and mortality worldwide. The term is inclusive of traumatic brain injury, cerebral ischemia, subarachnoid hemorrhage, and intracerebral hemorrhage. Current pharmacologic treatments have had minimal effect on improving neurological outcomes leading to a significant interest in the development neuroprotective agents. Minocycline is a second-generation tetracycline with high blood brain barrier penetrance due to its lipophilic properties. It functions across multiple molecular pathways involved in secondary-injury cascades following acute brain injury. Animal model studies suggest that minocycline might lead to improved neurologic outcomes, but few such trials exist in humans. Clinical investigations have been limited to small randomized trials in ischemic stroke patients which have not demonstrated a clear advantage in neurologic outcomes, but also have not been sufficiently powered to draw definitive conclusions. The potential neuroprotective effect of minocycline in the setting of traumatic brain injury, subarachnoid hemorrhage, and intracerebral hemorrhage have all been limited to pilot studies with phase II/III investigations pending. The authors aim to synthesize what is currently known about minocycline as a neuroprotective agent against acute brain injury in humans.